MOTION CUEING SYSTEM FOR TRAIN SIMULATOR - INDRA AULIA - NIM: 13214100 , ACHMAD
The needs of train simulator in Indonesia arise for the training of train drivers as the train usage grows. The designed train simulator consists of the visual system and the platform movement control system. Motion cueing is the system which calculates the platform’s position to produce the feeling of real train locomotive movement to the user while also considers the 3-degree-of-freedom platform’s mechanical restrictions in its calculation and algorithm. Classical Washout Filter (CWF) is the motion cueing algorithm used in this project. CWF consists of filters, scale and limit, tilt rate coordination, tilt rate limiter, and integrator. This book explains the design, implementation, and verification of each element in the motion cueing and the motion cueing system itself is also tested in this book. The implemented motion cueing is able to give train movement sensation to the user with 10% steady-state error for surge and sway train movement and transient error for train pitch and roll position : the difference in settling time is 0.144 second for pitch perception while the difference in rise time is 0.036 second and settling time difference is 0.072 second for roll perception. The motion cueing system is also ready to be implemented in the simulator system which has 36 ms as its sampling period.